Case Report: Monitoring of a High-Risk Pregnancy in a Patient with Imminent Preterm Labor and a History of Poor Obstetric Outcomes - Bahari, Resma Putri; Ratih Kusuma Wardhani (Papua Medicine and Health Science, 2025)
Imminent preterm labor can lead to preterm birth, which is the leading contributor to perinatal morbidity and mortality worldwide, accounting for 70% of neonatal deaths. This study aims not only to reduce the incidence of preterm birth but also to improve the quality of care for pregnant women and support optimal fetal health. This research employed a qualitative design with a case study approach and was documented using Varney’s seven-step midwifery management process. The research subject was Mrs. L, a 23-year-old woman pregnant with her third child at 36–37 weeks of gestation, diagnosed with imminent preterm labor and a bad obstetric history. Data were collected through interviews and head-to-toe physical assessments conducted on the pregnant woman. The instruments used included an assessment form and the Puji Rohyati Score (a screening tool used to identify low-risk or high-risk pregnancies). Primary data were utilized. The conclusion drawn after approximately two hours of observation was that there was no progression of labor.